2022
DOI: 10.3390/biom12091231
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Response of Human Trabecular Meshwork Cells to Transforming Growth Factor-Beta 3 and Autotaxin in Aqueous Humor

Abstract: This study examines the potential role of transforming growth factor-beta 3 (TGF-β3) on the fibrotic response of cultured human trabecular meshwork (HTM) cells. The relationships and trans-signaling interactions between TGF-β3 and autotaxin (ATX) in HTM cells were also examined. The levels of TGF-β and ATX in the aqueous humor (AH) of patients were measured by an immunoenzymetric assay. The TGF-β3-induced expression of the fibrogenic markers, fibronectin, collagen type I alpha 1 chain, and alpha-smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…The effect of TGF-β3 on in vitro α-SMA expression, however, appears to vary depending on the model system. TGF-β3 treatment increased the expression of α-SMA mRNA or protein in cultured human trabecular meshwork cells, urinary tract stroma-derived fibroblasts, human uterine fibroid smooth muscle cells, and 3D cultured human corneal fibroblasts (although to a lesser degree than TGF-β1) [73][74][75][76]. In contrast, TGF-β3 treatment in concentrations of 1-100 ng/mL did not increase α-SMA protein content in bovine keratocyte or wounded corneal organ cultures, although TGF-β1 did [77].…”
Section: Fibrogenesis In Vitro and In Bone Marrow-spared Animalsmentioning
confidence: 99%
“…The effect of TGF-β3 on in vitro α-SMA expression, however, appears to vary depending on the model system. TGF-β3 treatment increased the expression of α-SMA mRNA or protein in cultured human trabecular meshwork cells, urinary tract stroma-derived fibroblasts, human uterine fibroid smooth muscle cells, and 3D cultured human corneal fibroblasts (although to a lesser degree than TGF-β1) [73][74][75][76]. In contrast, TGF-β3 treatment in concentrations of 1-100 ng/mL did not increase α-SMA protein content in bovine keratocyte or wounded corneal organ cultures, although TGF-β1 did [77].…”
Section: Fibrogenesis In Vitro and In Bone Marrow-spared Animalsmentioning
confidence: 99%
“…TGF-β3 is a member of multifunctional peptide superfamily, regulates cell growth and differentiation, and exerts a special role in tissue fibrosis ( Liu et al, 2022b ). For example, Liu et al reported that Vgll3 could positively regulate the expression of the key pro-fibrotic factor TGF-β3 and the downstream factor smad2/4.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%